The Role of Code-Switching Implementation in Teaching Explanation Text for Secondary School (Proceedings of English Linguistics and Literature, 2022)
This research aim of this study is to explore the implementation of code-switching in explanation text in TEFL classrooms of secondary school. This research was conducted at a teacher college, and the candidate of an English teacher is the research subject. In this study, the researcher explores the different types, processes, and factors that led to the occurrence of teacher code-switching in an English classroom. English teacher candidate at teacher college. This research uses qualitative research. The instruments used are observation and interview. The researcher observed classroom interactions where various topics are being taught. Listening, speaking, reading, and writing is the four skills. The subject is interviewed to find out why they are saying and what they are saying. An interview with the subject is conducted to determine why they are using code-switching in teaching English. The data is analyzed using code-switching theory. According to the findings, the teaching used three types of code-switching in the teaching: intra-sentential switching, inter-sentential switching, and tag switching. In the sentence, there is code-switching in the processing time from English to Bahasa Indonesia and vice versa. Code-switching is triggered by a number of factors, including the teacher's education, experience, attitude, and translation method. While the external factor that caused code-switching is the students' English proficiency. The research findings presented in the study will show the voice of English teachers in describing explanation text using code-switching, and analyzing the implementation and usage of code-switching in EFL classrooms.